As implicações do processo de Bolonha na formação de professores: um estudo nas Escolas Superiores de Educação em Portugal - Brito, Elisabete; Rodrigues, Florbela; Simões, Fátima (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This work results from an investigation on the creation of new courses for Teacher Training in Portugal. The aim was to analyze the implications of the Bologna Process in Teacher Training Colleges of the existing Portuguese public education. In order to assess how these changes were operationalized, understand their effects in these courses and hence the future exercise of teaching profession in Portugal.Methodologically, a documentary analysis of implementation reports of the Bologna process was held to the polytechnic institutions offering Teacher Training.The conclusion is that the creation of these formations was maturely insufficient when elaborating the studies plan presented hastily, most due to the late promulgation of the legal framework that defined them, which resulted in several legislative conflicts.
Keywords: teacher training; the Bologna process; official documents